PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MEDIA ICT DAN MEDIA GRAFIS DENGAN MEMPERHATIKAN MINAT - Maulida Purnama Sari; Tedi Rusman; Nurdin Nurdin (FKIP Unila, 2016)
The purpose of this study was to determine differences in learning outcomes using ICT media and graphic media by considering the students interest in learning. The method used in this research was a comparative study with the experimental approach, testing the hypothesis, it was using two-way analysis of variance formula and t-test of two independent samples. Based on the result of data analysis, it obtained the results as follows: (1) There are differences in learning outcomes of students who use ICT media compared with the use of graphic media. (2) Results of learning using ICT media is higher than the class of graphic media on students who have a high interest in learning. (3) Results of learning using ICT media is lower than the class that uses the graphic media on students who to their learning outcomes. (4) There is an interaction between the learning media usage with the student interest on learning outcomes.Tujuan dari penelitian ini adalah untuk mengetahui perbedaan hasil belajar menggunakan media ICT dan media Grafis dengan memperhatikan minat belajar. Metode yang digunakan dalam penelitian ini adalah penelitian komparatif dengan pendekatan eksperimen, Pengujian hipotesis menggunakan rumus analisis varians dua jalan dan t-test dua sampel independen. Berdasarkan analisis data diperoleh hasil sebagai berikut: (1) Terdapat perbedaan hasil belajar siswa yang menggunakan media ICT dibandingkan dengan yang menggunakan media grafis. (2) Hasil belajar menggunakan media ICT lebih tinggi dibandingkan menggunakan media Grafis pada siswa yang memiliki minat belajar tinggi. (3) Hasil belajar menggunakan media ICT lebih rendah dibandingkan dengan kelas yang menggunakan media Grafis pada siswa yang memiliki minat belajar rendah. (4) Terdapat interaksi antara penggunaan media pembelajaran dengan minat belajar siswa.Kata kunci: hasil belajar, mata pelajaran ekonomi, media ict, media grafis, minat belajar.